An Analysis of Students’ Speaking Ability in Retelling Story on Descriptive Text at D3 Midwifery - Harahap, Yulinda Oktaviana; Harahap, Yulina Oktaviani (PT Inovasi Pratama Internasional, 2025)
This research aimed to assess students' speaking abilities and identify the most common issues faced by students at Akbid Baruna Husada Sibuhuan. This research analysed students' speaking challenges based on five components: pronunciation, grammar, vocabulary, fluency and comprehension. This research was conducted qualitatively. The number of samples obtained only 21 students. The researchers employed a speaking exam. The Instrument for research. This study used video students' performance when retelling descriptive material. Then the researcher transcribed the videos into scripts and asked raters to submit scores. The study indicated that students' speaking ability in repeating stories had an average score of 3, indicating a good level. The articulation component, the students' cruel score was 2.8 focuses, where as linguistic use got 3.5 focuses. Taking after that, lexicon component was 3.2 focuses, then again on familiarity, it was 2.7 focuses. The final, the students' normal score on the component of comprehension was 2.8 focuses. At long last, it can be concluded that the most prevailing issue confronted by understudies in talking was the familiarity component.